Empathy, Social Dominance Orientation, Mortality Salience, and Perceptions of a Criminal Defendant - Donna Crawley; Richard Suarez (SAGE Open, 2016)
In two studies, participants completed measures of trait empathy and social dominance orientation, read a summary of a hit and run trial, and provided reactions to the case. In Study 1, the three randomly assigned conditions included a prompt to empathize with the victims, the empathy prompt with a mortality salience manipulation, and a control condition. Participants high in trait empathy were harsher in their judgments of the defendant than were low empathy participants, particularly after having read the mortality salience prompt. The results indicated that mortality salience had triggered personality differences. Participants high in social dominance assigned harsher sentences across conditions. Study 2 involved the same paradigm, but the prompts were presented on behalf of the defendant. Despite the pro-defendant slant, the pattern of results was similar to Study 1. Differences by trait empathy were more apparent among participants experiencing mortality salience, and social dominance was related to sentence choices. There were no indications in either study of mortality salience increasing bias against defendants in general or increasing racial bias.